A Combined Approach of AHP and TOPSIS for Realiability (International Journal of Food and Nutritional Sciences, 2022)
With more corporate industries utilizing internet services to communicate vital information over the World Wide Web, reliability has become a demanding topic. Systems that are dependable are crucial in this scenario. Therefore, the majority of the industry is concerned with system reliability. The high dependability of systems has been addressed by numerous strategies over the past ten years, yet the majority of these methodologies are either speculative or impractical. The motivation behind the review was to investigate the legitimacy and plausibility of the model utilizing AHP & TOPSIS. Here, we employed a particular multi-criteria decision-making technique known as the Analytic Hierarchy Process (AHP) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). This framework will help the development team to choose the best reliability mode for each situation the basis of predictability.